Removal Of Humic Acid From Water Using An Ozonation Alone And Combination Of Ozonation And Adsorption - Dhiwya, Paramasivam (Universiti Sains Malaysia, 2022)
This study evaluates the performance of ozonation alone and hybrid ozonation process in where ozonation coupled with activated carbon and lava rocks respectively. The removal of humic acid was evaluated by UV254 absorbance. When ozonation was used alone, the removal was 54.91% at a humic acid concentration of 10 mg/L, pH 7 and oxidation time of 20 minutes. The results showed that the use of activated carbon as an adsorbent increased the removal of humic acid compared to ozonation alone as it can act as adsorbent and catalyst. The removal efficiency was 96.36 % at oxidation time of 20 minutes, pH 7 and catalyst loading of 1 g/L. The oxidation experiment was also carried out using lava rocks and the removal efficiency was 76.76 % at oxidation time of 20 minutes, pH 7 and loading of 5g/L. This indicates that ozonation coupled with activated carbon is highly effective compared to lava rocks. In conclusion, hybrid ozonation process yields better compared to ozonation alone.